Orthokeratinized Odontogenic Cyst: A Report of Three Clinical Cases - María del Carmen González Galván; Abel García-García; Eduardo Anitua-Aldecoa; Rafael Martinez-Conde Llamosas; José Manuel Aguirre-Urizar (Case Reports in Dentistry)
The orthokeratinized odontogenic cyst (OOC) is a rare developmental odontogenic cyst that has been considered as a variant of the keratocystic odontogenic tumour (KCOT) until Wright (1981) defined it as a different entity. Surgery is the usual treatment, and recurrence or association with Gorlin-Goltz syndrome has rarely been described. In this report, we presented three cases of this pathology, and we review the principal clinical, histological, radiological, and therapeutic aspects. Case 1. A 73-year-old female presents with a slight swelling on the right mandible, associated with an unilocular well-defined radiolucent lesion. Case 2. A 27-year-old female presents with a painful mandibular swelling associated with an unilocular radiolucent lesion posterior to the 4.8. Case 3. A 61-year-old male was casually detected presents with an unilocular radiolucent lesion distal to the 4.8. Conclusion. The OOC is a specific odontogenic clinicopathological entity that should be differentiated from the KCOT as it presents a completely different biological behaviour.